Laparoscopy has a therapeutic role in the management of abdominal trauma: A matched-pair analysis. (August 2017) - Chakravartty, Saurav; Sarma, Diwakar R.; Noor, Muhammad; Panagiotopoulos, Spyros; Patel, Ameet G.
Abstract: Introduction: Laparoscopy is increasingly utilised as a diagnostic tool in management of abdominal trauma; however its role in therapeutic intervention remains unexplored. The aim of this study is to compare laparoscopy with laparotomy in the treatment of abdominal trauma in haemodynamically stable patients. Methods: A review of patients undergoing surgery for abdominal trauma between January 2004–2014 identified 25 patients who underwent laparoscopy for therapeutic intervention (TL). This group was matched with 25 similar patients undergoing laparotomy (LT). Matching of the two cohorts was based on patient characteristics, severity of injuries, haemodynamic compromise and radiological findings. Peri-operative outcomes were compared. Discussion: Patient characteristics were similar in TL and LT patients for age (median 33 vs. 26 years), gender distribution and clinical presentation. Injury severity score was also similar with a median of 16 in both groups (major trauma = ISS>15, normal range 0–75). Types of injuries included; hollow viscus [bowel repair = 10 (TL) vs. 16 (LT)] and solid organs [5(TL) vs. 2 (LT)]. Median operating time was similar in both groups; 105(TL) compared to 98 (LT) minutes. Post-operative complications (1 vs. 10, p = 0.02), analgesia requirements, specifically opiate use (34 vs. 136 morphine equivalents, p = 0.002) and hospital stay (4 vs. 9 days, p = 0.03) were significantly lower in the laparoscopy group. Conclusions: Abdominal trauma in haemodynamically stable patients can be managed effectively and safely with laparoscopy by experienced surgeons. Major benefits may include lower morbidity, reduced pain, and shorter length of hospital stay. Highlights: Laparoscopic therapeutic surgery in stable trauma patients is controversial. Laparotomy and laparoscopy with definitive surgery were matched and compared. Laparoscopy for definitive treatment was safe in abdominal trauma. Laparoscopy is less morbid, painful and shortens hospital stay. Therapeutic laparoscopy leads to improved care in stable trauma patients.